Entre o prazer e a dor: uma etnografia em contextos digitais de dominação feminina - Barbosa, Bruno Henrique Benichio Alves (Universidade Federal de São Carlos, 2021)
The purpose of the present research is to analyze the erotic practices in the context of Brazilian BDSM. As an analytical cut, I chose Female Domination, which is configured as one of the sexual role categories of the BDSM community (Bondage / Discipline, Domination / Submission or Sadism / Masochism). Dominant women use digital media to promote spaces of sociability, to legitimize their sexuality, and to textualize the desires and dilemmas that surround their daily lives. Through the multidisciplinarity of contemporary studies in digital contexts, this research conducted a digital ethnography of three blogspots to achieve an understanding of what Female Domination is, what experiences of gender and sexuality are related to these performances, and what are the goals that drive Female Dominators to use digital media. Furthermore, I mobilize as theoretical references the concepts of Judith Butler and Michel Foucault to analyze the intensity with which these practices are configured in a convergent and/or divergent way, in relation to normative systems about sex, gender, and desire and I use Eva Illouz's sociological propositions about love and emotions as a theoretical basis to understand the affective relationships that are waged within Female Domination.
Between pleasure and pain: an ethnography in digital contexts of female domination
Entre el placer y el dolor: una etnografía en contextos digitales de dominación femenina
Keywords: BDSM; Etnografia digital; Mídias digitais; Gênero; Sexualidade; Digital ethnography; Digital media; Gender; Sexuality; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS